Records Management Practices in Public Institution Archives - Hanis Kamarudin, Nurul; Fairuk Mat Yatin, Saiful; Mohd Yunus, Alwi; Azwan Azman, Kamarul; Md Jali, Jafalizan; Md Zali, Mastura (International Journal of Engineering and Technology, 2018)
The purpose of this study is to explore about records management practices in public institution archives. Identification types of records, policy, procedure, filing system and records management system is among the most important aspect in managing a record in the archives. This article was based on one propose case study that will be conducted in one of the public institution archives. The objectives of this case study are aiming to identify types of records kept, the policy and procedure used, the filing system and records management system used in one of the public institution archives in Malaysia. All objectives is to give awareness about the importance ofÂ good records management practices in ensuring all archival material collections of public institution archives can be protected for future reference. Future findings from this study can become a guide for proper records management practices, particularly in academic institutions, which are still lacking in Malaysia.Â Â